Functional Characterization of Deubiquitinase UBP Family and Proteomic Analysis of Aaubp14-Mediated Pathogenicity Mechanism in Alternaria alternata - Jiejing Tang; Hang Zhou; Chen Jiao; Hongye Li (Journal of Fungi, 2025)
The Alternaria alternata tangerine pathotype causes Alternaria brown spot, a devastating disease of susceptible tangerine varieties and their hybrids. Alternaria citri toxin (ACT) is the primary virulence factor, but the regulatory mechanisms governing ACT synthesis remain unclear. Deubiquitinating enzymes maintain ubiquitination homeostasis and regulate fungal pathogenicity, yet their role in A. alternata remains unexplored. We characterized 13 ubiquitin-specific protease (UBP) family members in A. alternata tangerine pathotype. Six UBP genes (Aaubp2, Aaubp3, Aaubp4, Aaubp6, Aaubp14, and Aaubp15) regulated mycelial growth. Aaubp14 deletion abolished sporulation, while mutations of Aaubp3, Aaubp4, Aaubp6, Aaubp8, and Aaubp15 altered conidial morphology. qRT-PCR demonstrated distinct host-induced expression patterns among Aaubp genes. Pathogenicity tests showed that ΔAaubp6, ΔAaubp14, and ΔAaubp15 mutants failed to produce lesions on Citrus reticulata cv. Hongjv leaves. Moreover, Aaubp14 deletion significantly suppressed ACT biosynthesis gene expression and blocked ACT production. Comparative proteomics showed Aaubp14 regulates ACT biosynthesis by modulating protein ubiquitination in metabolic pathways and controls pathogenicity via a complex network. Our findings elucidate Aaubp gene function in development and pathogenicity, particularly the Aaubp14-mediated regulation mechanism, providing insights into ubiquitination-mediated pathogenicity in phytopathogenic fungi.